Answer:
The answer is below
Explanation:
Given that f(x)=x(22-x)
a) f(x)=x(22-x)
f(x + h) = (x + h)(22 - (x + h))
f(x + h) = (x + h)(22 - x - h)
f(x + h) = (22x - x² - xh + 22h - xh - h²)
f(x + h) = (-x² + 22x - h²+ 22h - 2xh)
b) f(x)=x(22-x) = 22x - x²
f(x + h) = (-x² + 22x - h²+ 22h - 2xh)
f(x+h)- f(x) = (-x² + 22x - h²+ 22h - 2xh) - (22x - x²)
f(x+h)- f(x) = -x² + 22x - h²+ 22h - 2xh - 22x + x²
f(x+h)- f(x) = -x² + x² + 22x - 22x - h²+ 22h - 2xh
f(x+h)- f(x) = - h²+ 22h - 2xh
c) f(x+h)- f(x) = - h²+ 22h - 2xh
![(f(x+h)-f(x))/(h)=(- h^2+ 22h - 2xh)/(h)\\ \\(f(x+h)-f(x))/(h)=(- h^2)/(h)+(22h)/(h)-(2xh)/(h)\\\\(f(x+h)-f(x))/(h)=-h+22-2x](https://img.qammunity.org/2021/formulas/mathematics/college/h9bgu7ang0ei737vxndrtc06fha9r9jcwd.png)
![\lim_(h \to 0) (f(x+h)-f(x))/(h)= \lim_(h \to 0) (-h+22-2x )=22-2x](https://img.qammunity.org/2021/formulas/mathematics/college/vwvxxocmzkiw4juxh7sromh9w8b64ejzjq.png)